A potential therapeutic approach for ulcerative colitis: targeted regulation of macrophage polarization through phytochemicals - Wang, Ke; Mao, Tangyou; Lu, Xinyu; Wang, Muyuan; Yun, Yifei; Jia, Zeyu; Shi, Lei; Jiang, Haoxi; Li, Junxiang; Shi, Rui (Frontiers in Immunology, 2023)
Ulcerative colitis (UC), a type of inflammatory bowel disease characterized by recurrent and incurable, has brought huge pain and economic losses to patients due to the limited treatment methods available. Thus, it is urgent to develop a new and promising strategies as well as safe and effective drugs for UC clinic treatment. Macrophages act as the first line of defense in the maintenance of intestinal immune homeostasis, whose phenotypes transformation has a great impact on the development of UC, and studies have proved that targeting macrophage polarized to M2 phenotype is an effective strategy for UC prevention and treatment. Phytochemicals extracted from natural plants have attracted attention of research due to special biological activity and nutritional value, which are confirmed to exert preferable protective benefits against colonic inflammation. In this review, we described the effect of macrophage polarization on the development of UC and gathered the great potential of natural products in recent years to target the phenotype of macrophages and the possible mechanism of action in the UC treatment, which may provide more updated directions and references for clinical therapy of UC.